KEWARGANEGARAAN DAN DILEMA MINORITAS PASCA KOLONIAL BERCERMIN KASUS SABAH DAN KESULTANAN SULU Ahmad Suaedy AW Centre-Universitas Indonesia Email: suaedy@ - Suaedy, Ahmad (Universitas Hasanuddin, 2014)
This paper is aimed to understand the issue of citizenship and the post colonial minority dilema by looking ath the issue of Sabah and the Sultanate of Sulu. Unlike western countries whosestates were formed based on their established historical territories, the formation of states in the east or non-western areas in general inherited complicated religious, ethnic, traditional rules and familial relations. Non-western post-colonial states should developed different conceptions ofstate-borders by considering traditional cutural realities, multicultural and plural ethnicities, languages and religions and family connections within each state or among several states. This re-defintion should not eliminate individual ownership but also to promote a vision of commonwelfare.Keywords: Citizenship, Minority, Sabah, Sulu Sultanate